Founder‐CEOs and corporate turnaround among declining firms. (23rd November 2017) - Abebe, Michael A.; Tangpong, Chanchai
Abstract: Manuscript Type: Empirical Research Question/Issue: Despite the growing interest in leaders' role in the turnaround process, there is a paucity of research on founder‐CEOs' role in achieving successful turnaround among declining firms. In this study, using insights from the organizational identification literature, we argue that founder‐CEOs play an important role in turnaround attempts due to their strong organizational commitment and psychological attachment to the declining firm as well as the relative absence of agency problem issues common among their non‐founder counterparts. Research Findings/Insights: Using data from a matched pair sample of 142 US firms that experienced performance decline, we found that founder‐CEO leadership significantly increases turnaround success in declining firms. We also found that, among turnaround firms, those led by founder‐CEOs tend to put more emphasis on market‐based turnaround strategies, such as new product introductions, and less emphasis on retrenchment actions, such as divestments. Theoretical/Academic Implications: Our findings contribute to corporate turnaround research by providing a more nuanced view of leaders' role in the turnaround process by specifically exploring the effect of founder CEO leadership. Furthermore, this study contributes to the turnaround literature by highlighting the strategic choices of founder‐CEO‐led firms and how these choices influence successful turnaround. Finally, by introducing organizational identification perspective, this study provides additional theoretical explanation of leadership antecedents of successful turnarounds. Practitioner/Policy Implications: The findings of this study suggest that boards of directors, shareholders, and consultants who often participate in turnaround management should carefully consider retaining founder‐CEOs and endorsing their leadership during the turnaround process. Further, the findings provide turnaround specialists and other stakeholders with further understanding of not only the importance of product market strategies in the turnaround process but also founder‐CEOs' role in fostering such strategies.